The financial times essential guide to writing a business plan : how to win backing to start up or grow your business - Evans, Vaughan (Harlow, England ; New York, NY : Pearson, 2022)
'This book will show you how to design, craft and shape a plan to the needs of your backer. It places great emphasis on the specific challenges faced by start-ups, has new chapters on pitching the plan and performing against plan and new appendices on alternative sources of finance, an example business plan in its entirety and what to read next. This edition also adds sections on certain issues which backers today are keen to see addressed, for example social media marketing and the influence of influencers and energy conservation'--
Includes bibliographical references and index.
Keywords: Business planning; Proposal writing in business